Estimation Method and Verification of Pressure in Supersonic Inlet - LI Qiang; CAO Xiaolong (Hangkong gongcheng jinzhan, 2020)
Prediction and limitation of inlet pressure are important for supersonic vehicles. Numerical simulation on high speed inlet flow is conducted, and pressure characteristics with different Mach numbers, attack angles, yaw angles and excess air coefficients is analyzed. Based on dimensionless and decoupled method, empirical formula for high speed inlet pressure is fitted and verified by flight results. The results show that, with the Mach number increasing and excess air coefficient decreasing, the pressure in inlet increases. Attack angle and yaw angle have little influence on inlet pressure in normal work envelope. The inlet pressure estimated by empirical formula is in good agreement with measured data in flight tests, which means that the formula established in this paper has a high precision.